Harnessing Knowledge for Improving Access to Fruits and Vegetables at Farmers Markets: Interactive Data Visualization to Inform Food Security Programs and Policy. - Johnson, Matilda O.; Cozart, Thometta; Isokpehi, Raphael D. (Health Promotion Practice, 2020)
High consumption of fruits and vegetables leads to decreased risk of various chronic diseases, including obesity and cardiovascular disease. Community-level barriers to access fruits and vegetables include the high cost, limited availability, and transportation. Farmers markets are a priority strategy for improving community access to fresh fruits and vegetables. The U.S. Department of Agriculture (USDA) National Farmers Market Directory is a voluntary self-reported data source on farmers markets. The objective of this investigation of the USDA farmers markets data directory was to determine how farmers markets in the United States are grouped according to (1) availability of fruits and vegetables and (2) the payment accepted. We designed and implemented interactive data visualizations in visual analytics software to understand access to fruits and vegetables at farmers markets from 8,497 entries in the USDA Farmers Market Directory. Among the 665 new or updated entries in year 2018, a subset of 641 (96%) farmers markets with availability of fresh fruits and vegetables had 16 subgroups. Additionally, a subgroup of 102 (16%) farmer markets accepted all four federal nutrition assistance benefits (SFMNP, SNAP, WIC CVVs, and WIC FMNP). The interactive data visualizations including geographic maps connected to social media resources can be useful in advocacy efforts and can inform policy improvements designed to improve physical, social, and economic access to fruits and vegetables at farmers markets.